Long-term exposure to ambient fine particulate matter and incidence of diabetes in China: A cohort study. (May 2019) - Liang, Fengchao; Yang, Xueli; Liu, Fangchao; Li, Jianxin; Xiao, Qingyang; Chen, Jichun; Liu, Xiaoqing; Cao, Jie; Shen, Chong; Yu, Ling; Lu, Fanghong; Wu, Xianping; et al.
Abstract: Background: Diabetes caused substantial economic and health burden worldwide. However, the associations between air pollution and diabetes incidence were rarely reported in the developing countries, especially in China with relatively high PM2.5 concentrations. Objectives: A cohort-based study was conducted to assess the diabetes incidence associated with long-term exposure to ambient PM2.5 . Methods: We collected individual health data and risk factors from the project of Prediction for Atherosclerotic Cardiovascular Disease Risk in China (China-PAR Project) from 15 provinces over China. Diabetes was defined as fasting glucose levels ≥7.0 mmol/L at the follow-ups and/or the use of insulin or oral hypoglycemic agents and/or diagnosed medical history of diabetes during 2004 to 2015. Individual-level PM2.5 exposures were estimated from satellite-based PM2.5 concentrations (10 km spatial resolution) during the study period. Cox proportional hazards models with random intercepts of each cohort and region were employed to estimate the diabetes incidence attributable to PM2.5, after the adjustment for age, gender, body mass index, smoking status, education, work-related physical activity level, hypertension, urbanicity, county-level averaged years of education, and long-term levels of temperature and relative humidity. Results: A total of 88, 397 subjects were analyzed with 580, 928 person-years of follow-up after 2004, among which 6439 new cases of diabetes were observed. The mean age of the subjects was 51.7 years at baseline. For an increase of 10 μg/m 3 in long-term PM2.5 exposure, the multivariable-adjusted percent increase in the diabetes incidence was estimated to be 15.66% (95% confidence interval: 6.42%, 25.70%). The adverse effects of PM2.5 were larger among females, rural subjects, non-smokers, normotensives, subjects younger than 65 years and subjects with body mass index <25 kg/m 2 . Conclusions: Our findings provided evidence for the association of long-term exposure to PM2.5 with diabetes incidence in China. A sustained improvement of air quality will benefit the reduction for diabetes epidemic in China. Highlights: The largest study in China to study the effect of PM2.5 on diabetes incidence. A national study focus on the general Chinese population. Satellite-based PM2.5 levels were used for long-term exposure assessment. Long-term exposure to PM2.5 was positively associated with diabetes incidence.